An integer programming formulation for a fair tournament scheduling in TeamGym in Iceland - Andrea Valdimarsdóttir 1994- (2021)
Organizing a sports tournament schedule can be challenging and time-consuming. In this project, the process of generating a TeamGym tournament schedule is automated. Today, the tournaments at FSÍ are made manually. By automating the process, the time for making the tournaments at FSÍ should be considerably shortened and reduce the risk of errors. The main goal of this project is to create a mathematical model that ensures a fair tournament for all teams while fulfilling specific requirements such as all teams must compete once on each event, each round should preferably contain all types of events and care must be taken that teams' rest periods are within the agreed time frame. The results of the project show that a fair and feasible solution can be found with automation that decreases the scheduling time and ensures a fairer and better-organized tournament. Keywords: Tournament schedule, gymnastics, TeamGym, optimization model. Það getur verið krefjandi og tímafrekt að útbúa íþróttamótsplön. Í þessu verkefni er ferlið við að útbúa hópfimleikamótsplan gert sjálfvirkt. Í dag eru fimleikamótin hjá FSÍ gerð handvirkt en með því að gera ferlið sjálfvirkt ætti tíminn við gerð fimleikamóta hjá FSÍ að styttast til muna ásamt því að minnka líkur á villum. Markmið þessa verkefnis er að útbúa stærðfræðilíkan sem tryggir sanngjarnt mót fyrir öll lið en á sama tíma þarf að fara eftir ákveðum skilyrðum. Dæmi um slík skilyrði eru að öll lið þurfa að keppa einu sinni á hverju áhaldi, hver umferð á helst að innihalda allar gerðir áhalda og passa þarf að hvíldartími hvers liðs sé innan ákeðins tímaramma. Niðurstöður verkefnisins gefa til kynna að hægt er að búa til sanngjarnari og hagkvæmari lausn sem er sjálfvirk og tekur mun styttri tíma að útbúa. Efnisorð: Mótsplan, fimleikar, TeamGym, bestunarlíkan.